Preparation of Molecularly Imprinted Regenerated Cellulose Composite Membranes by Surface-Initiated Atom Transfer Radical Polymerization Method for Selective Recognition of Lysozyme - Chaoli Wang; Xiaoling Hu; Ping Guan; Danfeng Wu; Longfei Yang; Chunbao Du (Adsorption Science & Technology)
Novel types of polymeric membranes containing molecular recognition sites for selective recognition of lysozyme (Lyz) have been prepared using a surface-initiated atom transfer radical polymerization approach. The surface compositions of the regenerated cellulose (RC) membranes before and after polymerization were characterized by X-ray photoelectron spectroscopy analysis, which demonstrated that the molecular imprinting layer was successfully fabricated onto the surface of RC membranes. The selective recognition of Lyz molecularly imprinted membranes (Lyz–MIMs) for Lyz was evaluated by protein adsorption penetration tests. It was found that Lyz–MIMs have excellent adsorption capacity and specific recognition for Lyz adsorption from aqueous solutions. In the presence of competitive substances, a separation factor of 23.08 was achieved. The molecularly imprinted RC composite membrane is promising for separation and purification of specific protein compositions in biosamples. In addition, it may have good prospect for enriching target protein, which requires further study.